Biologically Important Areas II for cetaceans within U.S. and adjacent waters – Gulf of Alaska Region - Lauren A. Wild; Heather E. Riley; Heidi C. Pearson; Christine M. Gabriele; Janet L. Neilson; Andy Szabo; John Moran; Janice M. Straley; Sarah DeLand (Frontiers in Marine Science, 2023)
We delineated and scored Biologically Important Areas (BIAs) for cetacean species in the Gulf of Alaska region. BIAs represent areas and times in which cetaceans are known to concentrate for activities related to reproduction, feeding, and migration, and also the known ranges of small and resident populations. This National Oceanic and Atmospheric Association (NOAA)-led effort uses structured expert elicitation principles to build upon the first version of NOAA’s BIAs for cetaceans. Supporting evidence for these BIAs came from aerial-, land-, and vessel-based surveys; satellite-tagging data; passive acoustic monitoring; Indigenous knowledge; photo-identification data; and/or prey studies. A total of 20 BIAs were identified, delineated, and scored for six species: beluga whale ( Delphinapterus leucas ), fin whale ( Balaenoptera physalus ), gray whale ( Eschrichtius robustus ), humpback whale ( Megaptera novaeangliae ), North Pacific right whale ( Eubalaena japonica ), and sperm whale ( Physeter macrocephalus ). Of the 20 total BIAs, there were two small and resident populations, one migratory, and 17 feeding areas; no reproductive BIAs were identified. An additional five watch list areas were identified, a new feature to the second version of BIAs. In addition to more comprehensive narratives and maps, the BIA II products improve upon the first version by creating metadata tables and incorporating a scoring and labeling system which improves quantification and standardization of BIAs within and across regions. BIAs are compilations of the best available science and have no inherent regulatory authority. They have been used by NOAA, other federal agencies, and the public to support planning and marine mammal impact assessments, and to inform the development of conservation measures for cetaceans.

Sharp decline in humpback whale (Megaptera novaeangliae) survival and reproductive success in southeastern Alaska during and after the 2014–2016 Northeast Pacific marine heatwave - Christine M. Gabriele; Courtney L. Amundson; Janet L. Neilson; Janice M. Straley; C. Scott Baker; Seth L. Danielson (Mammalian Biology, 2022)

Advanced image recognition: a fully automated, high-accuracy photo-identification matching system for humpback whales - Ted Cheeseman; Ken Southerland; Jinmo Park; Marilia Olio; Kiirsten Flynn; John Calambokidis; Lindsey Jones; Claire Garrigue; Astrid Frisch Jordán; Addison Howard; Walter Reade; Janet Neilson; et al. (Mammalian Biology, 2022)

Humpback whales interfering when mammal‐eating killer whales attack other species: Mobbing behavior and interspecific altruism? - Robert L. Pitman; Volker B. Deecke; Christine M. Gabriele; Mridula Srinivasan; Nancy Black; Judith Denkinger; John W. Durban; Elizabeth A. Mathews; Dena R. Matkin; Janet L. Neilson; Alisa Schulman‐Janiger; Debra Shearwater; et al. (Marine Mammal Science, 2017)
Humpback whales ( Megaptera novaeangliae ) are known to interfere with attacking killer whales ( Orcinus orca ). To investigate why, we reviewed accounts of 115 interactions between them. Humpbacks initiated the majority of interactions (57% vs . 43%; n = 72), although the killer whales were almost exclusively mammal‐eating forms ( MEKW s, 95%) vs . fish‐eaters (5%; n = 108). When MEKW s approached humpbacks ( n = 27), they attacked 85% of the time and targeted only calves. When humpbacks approached killer whales ( n = 41), 93% were MEKW s, and ≥87% of them were attacking or feeding on prey at the time. When humpbacks interacted with attacking MEKW s, 11% of the prey were humpbacks and 89% comprised 10 other species, including three cetaceans, six pinnipeds, and one teleost fish. Approaching humpbacks often harassed attacking MEKW s (≥55% of 56 interactions), regardless of the prey species, which we argue was mobbing behavior. Humpback mobbing sometimes allowed MEKW prey, including nonhumpbacks, to escape. We suggest that humpbacks initially responded to vocalizations of attacking MEKW s without knowing the prey species targeted. Although reciprocity or kin selection might explain communal defense of conspecific calves, there was no apparent benefit to humpbacks continuing to interfere when other species were being attacked. Interspecific altruism, even if unintentional, could not be ruled out.

Non‐lethal entanglement of humpback whales ( Megaptera novaeangliae ) in fishing gear in northern Southeast Alaska - Janet L. Neilson; Janice M. Straley; Christine M. Gabriele; Susan Hills (Journal of Biogeography, 2009)
Aim Entanglement in fishing gear is recognized as a potentially significant source of serious injury and mortality for humpback whales ( Megaptera novaeangliae ) in some parts of their range. In recent years, the number of humpback whales reported to have been entangled in Alaska has increased. In 2003–04 we quantified the prevalence of non‐lethal entanglements of humpback whales in northern Southeast Alaska (SEAK) with the ultimate goal of informing management discussions of the entanglement issue for the Central North Pacific stock of humpback whales. Location The near‐shore waters of northern Southeast Alaska. Methods We photographed individual humpback whales’ caudal peduncles as they dived and then examined the photographs for scars indicative of a previous entanglement. Results The percentage of whales assessed to have been non‐lethally entangled at some time in their lives ranged from 52% (minimal estimate) to 71% (conditional estimate) to 78% (maximal estimate). Of these, the conditional estimate is recommended because it is based solely on unambiguous scars. Eight per cent of the whales in one portion of the study area (Glacier Bay/Icy Strait) acquired new entanglement scars between 2003 and 2004, although the sample size was small. Calves were less likely than older whales to have entanglement scars, and males may be at higher risk than females. Whales with more photographs and/or photographic coverage may be more likely to be assessed as having been entangled than whales with fewer photographs and/or coverage. Main conclusions Caudal peduncle scars reveal that the majority of humpback whales in northern SEAK have been entangled. Comparison with statistics on reported entanglements suggests that most whales apparently shed the gear on their own, unless humans are disentangling whales much more often than is reported. While cumulative estimates of the percentage of whales with entanglement scars (e.g. the conditional estimate) provide useful baseline information, future efforts should focus on monitoring the annual rate of entanglement scar acquisition as a more powerful measure of contemporary entanglement rates. Our findings indicate that entanglement of humpback whales in fishing gear in SEAK is a management issue warranting increased attention. A proactive approach is needed to address the problem and to identify and implement preventive measures.

AGE AT FIRST CALVING OF FEMALE HUMPBACK WHALES IN SOUTHEASTERN ALASKA - Christine M. Gabriele; Janice M. Straley; Janet L. Neilson (Marine Mammal Science, 2007)